Generalizing fixed-priority scheduling for better schedulability in mixed-criticality systems - Chen, Yao; Shin, Kang G.; Xiong, Huagang (Information processing letters, 2016)
The design of mixed-criticality systems is often subject to mandatory certification and has been drawing considerable attention over the past few years. This letter studies fixed-priority scheduling of mixed-criticality systems on a uniprocessor platform but in a more general way, using different priority orderings in different execution phases and considering them collectively. Then a sufficient response-time analysis is developed and a new priority assignment scheme is proposed. This generalized approach has potential in better schedulability performance for mixed-criticality systems. •Different priority orderings are used to generalize mixed-criticality scheduling.•A response time analysis is developed to guarantee certification requirements.•A new priority assignment algorithm is proposed for determining task priority.•The proposed solution outperforms existing approaches in terms of acceptance ratio.